Impact of preoperative endoscopic ultrasound-guided fine needle aspiration on postoperative recurrence and survival in cholangiocarcinoma patients - Chafic, Abdul Hamid El; Dewitt, John; LeBlanc, Julia Kim; El Hajj, Ihab I; Cote, Gregory; House, Michael G; Sherman, Stuart; McHenry, Lee; Pitt, Henry A; Johnson, Cynthia; Mohamadnejad, Mehdi; Al-Haddad, Mohammad (Endoscopy, 2013)
Background and study aim: Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) is frequently performed for suspected biliary tumors for diagnosis and staging but carries a theoretical risk of needle-track seeding. We aimed to evaluate the impact of preoperative EUS-FNA on long-term outcomes for patients with cholangiocarcinoma (CCA).Patients and methods: In a retrospective single-center study of consecutive patients with CCA with preoperative EUS-FNA, main outcome measures were overall survival and progression-free survival. Results: In 150 patients with confirmed CCA, 61 underwent preoperative FNA. Median overall survival was 18.5 months (95 % confidence limits [CL] 15.4, 25.7): 111 patients died and 39 survived. Of the 150 patients, 119 underwent curative-intent surgical resection, with median progression-free survival of 17.8 months (95 %CL 14.5, 22.8); 89/119 patients had tumor recurrence or died, and 30/119 remained alive and disease-free. On multivariable analysis, overall survival was associated with: undergoing curative-intent surgery (hazard ratio [HR] 5.79, P = 0.001), lack of lymph node involvement (HR 1.89, P = 0.011), younger age (HR 1.51 for every 10 years, P < 0.0015), and small tumor size (HR 1.11 for every 1 cm, P = 0.029). For patients undergoing curative-intent surgery, on multivariable analysis, improved progression-free survival was associated with: lack of lymph node involvement (HR 1.88, P = 0.010), smaller tumor size (HR 1.16 for every 1 cm smaller, P = 0.003), and younger age (HR 1.53 for every 10 years, P < 0.001). Number of needle passes showed no statistically significant impact on overall survival.Conclusion: Preoperative EUS-FNA in patients with CCA does not appear to adversely affect overall or progression-free survival.